Supercritical carbon dioxide application using hydantoin acrylamide for biocidal functionalization of polyester - Orhan, Mehmet; Demirci, Fatma; Koçer, Hasan Basri; Nierstrasz, Vincent (Elsevier, 2020)
Biocidal functionalization in polyester fibers is a really tough challenge because of the lack of tethering groups. This study indicated supercritical carbon dioxide application using N-halamine would be an alternative solution for obtaining antibacterial function on the polyester surface. Firstly, N-(2-methyl 1-(4 methyl-2,5-dioxo-imidazolidin-4 yl)propan-2-yl)acrylamide was synthesized and applied to the polyester in supercritical carbon dioxide medium, at 120 degrees C, 30 MPa for different processing times. The addition of N-halamine on the surface significantly brought antibacterial activity against E. coli. The chlorine loadings showed that 6-h exposure time was critical to obtain sufficient antibacterial activity. This treatment caused a reasonable and tolerable loss in color and mechanical properties. But, the durability to abrasion, stability, and rechargeability of oxidative chlorine, and the durability of N-halamine on the surface were remarkably good. Conclusively, it can be available to work on polyester surfaces with resource-efficient and eco-friendly supercritical carbon dioxide technique for getting more functionalization and modification. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Supercritical carbon dioxide (scCO(2)); N-halamine; Polyester; Antibacterial surface modification